ANALISIS PENGEMBANGAN AIR BAWAH TANAH TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN SUMBERMANJING WETAN KABUPATEN MALANG - Andy Kristafi Arifianto (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
The purpose of this study was to describe the water flow, water requirement, water quality and satisfaction of society Subdistrict Sumbermanjing Wetan Malang Regency, analyze the effect of water flow, water requirement and water quality to the satisfaction of the people Subdistrict Sumbermanjing Wetan Malang Regency and to analyze between variable water flow, need for water and the water quality of the dominant influence on society satisfaction District of Sumbermanjing Wetan Malang Regency. The population in this study is the whole society Sumbermanjing Wetan District of Malang, amounting to 100.065 people. The number of samples in this study as many as 100 people. The sampling technique used in this study is simple random sampling. The analysis technique used is multiple regression analysis, F test and t test. Discharge water, water needs and water quality simultaneously significant effect on public satisfaction District of Sumbermanjing Wetan Malang Regency. This shows that the discharge of water plays a role in improving people's satisfaction and the better its water needs can lead to increasing people's satisfaction, as well as water quality perceived by the society of water is odorless, colorless, tasteless and tasted fresh able to increase community satisfaction. Discharge water, water needs and water quality is partially significant effect to the satisfaction of the District community Sumbermanjing Wetan Malang Regency. Water quality is dominant compared to variable water flow and water needs, which means that the main thing to consider in achieving the people's satisfaction is the quality of the water.